Energy Conversion in the Working Nozzle of a Pneumatic Abrasive-Jet Unit - Vadym Baha; Ján Piteľ (Журнал інженерних наук)
The article investigates the working processes in the channels with relatively simple geometry, such as working nozzles and seals designed to regulate the working flow jet passing through them. The main aim was to solve an essential scientific and technological problem of improving flow part nozzle performance in the pneumo-abrasive units by applying the results of the study of energy conversion mechanism, namely, the conversion of compressed air potential energy into kinetic energy of the nozzle outlet jet. Hydrodynamic methods of flow part profiling, CFD modeling, and a physical experiment were applied. The methods for rational choice of the working nozzle geometry and its operating mode were also carried out. The designs of working nozzles for hydro-pneumatic units, their systems, and elements were developed and improved. The air nozzle geometry was adapted to operate in the pneumo-abrasive unit, with the air abrasive mixture being its medium. River sand, with a grain size of about 0.5 mm, was used as an abrasive material. The numerical studies of the air-abrasive mixture flow in the nozzle flow part resulted in gaining detailed information about all the elements of its structure in the flow and beyond it within a wide range of operating modes due to the application of the ANSYS software. As a result, a new approach to working nozzles profiling based on providing a proper air-abrasive mixture flow movement with a minimum hydraulic axial and circumferential resistance was developed. This made it possible to increase both the air-abrasive mixture flow rate from a nozzle and its consumption factor value. The impact patterns of nozzle geometry and operating modes on its flow structure and other indicators considered while designing and upgrading the flow parts of the jet-abrasive nozzles were found. Overall, a new design for a working nozzle with better energy performance was developed.